Modified two-dimensional cracked finite element for crack identification - Kalanad, Aysha; Rao, B.N. (Journal of Structural Engineering, 2024)
In this paper two dimensional finite element with an embedded edge crack proposed by Potirniche et al. [Engineering Fracture Mechanics 75 (2008) 3895-3908] is modified for element crack depth ratios ranging up to 0.9 and for predicting natural frequency of a cracked beam more accurately. The element is implemented in the commercial finite element code ABAQUS as user element (UEL) subroutine. The accuracy of the UEL is verified by comparing the predicted first natural frequency with available experimental data. Subsequently a methodology to detect the crack location and size in conjunction with the proposed modified cracked element is presented.